A critical review on analysis of sand producing and sand-control technologies for oil well in oilfields - Xujiao He; Xujiao He; Zhanxi Pang; Lixin Ren; Lixin Ren; Liangdong Zhao; Xinqian Lu; Yanwei Wang; Pengcheng Liu (Frontiers in Energy Research, 2024)
Sand production in oil wells seriously affects the production of oil and gas in oilfields. Although conventional sand-control techniques can effectively prevent sand production, it may also limit the productivity of oil wells. Fracturing and packing sand control technology changes the distribution of pressure and flow in the wellbore, while foam polymer resin diversion technology reduces the anisotropy of reservoir permeability and increases the area of oil leakage in the reservoir, both achieving the goal of sand control and increased production. The sand-free production rate is successfully increased thanks to zeta potential sand control technology, which modifies the formation’s sand potential and causes the sand to agglomerate without harming the reservoir. This article first looks into the causes of sand production in oil and gas wells before examining the fundamentals, implementation strategies, and effects of traditional sand control techniques, fracturing and filling sand control technology, foam polymer resin diversion technology, and Zeta potential sand control technology. In this article, the experience of sand control technology in actual oil field applications is summarized, explained in detail, and the future development possibilities of sand control technology are discussed.